Central Banking and the Choice of Currency Regime in Accession Countries - Willem H. Buiter; Clemens Grafe (SUERF - The European Money and Finance Forum, 2001)
The subject matter of this paper is the design of appropriate Central Banking arrangements and exchange rate regimes for those former centrally planned Central and East European countries that are candidates for full membership in the European Union. We give an overview of the existing arrangements and point out to which extent monetary arrangements are restricted by conditions for entry both into the European Union and eventually into the European Monetary Union. Furthermore we investigate to which degree countries are fulfilling the accession criteria and compare their performance with the performance of earlier EU joiners like the countries of the Iberian Peninsula, Ireland and Greece. After concluding that the accession criteria do not necessarily favour a particular monetary regime, we analyse the pros and cons of the two regimes widely believed to be most stable- currency boards and inflation targeting. We find that under either regime tensions are likely to arise from the attempt to meet the accession criteria of a low inflation rate and a stable exchange rate. Due to likely large productivity gains in the traded goods sector the real exchange rate can be expected to display a trend real appreciation. Thus a currency board arrangement may well fail to produce an inflation rate below the Maastricht ceiling, unless the economy is run with a wasteful amount of spare capacity. Similarly the credibility of any inflation target would be undermined by the requirement that the exchange rate be kept within a specified target zone. This conflict could be resolved if the inflation ceiling was re-specified in terms of traded goods price inflation (and preferable in terms of ' core' traded goods price inflation) but this would require a change in the Maastricht Treaty.
Keywords: E58; E52; F15; F33; 330; Central Banks and their policies; Monetary policy; Financial integration; International monetary arrangements and institutions; Wechselkurssystem; Zentralbank; Optimaler Währungsraum; Currency-Board-System; Währungssubstitution; EU-Mitgliedschaft; Osteuropa